Applied Food Protein Chemistry 2014
DOI: 10.1002/9781118860588.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Proteins

Abstract: Designations used by companies to distinguish their products are often claimed as trademarks. All brand names and product names used in this book are trade names, service marks, trademarks or registered trademarks of their respective owners. The publisher is not associated with any product or vendor mentioned in this book.Limit of Liability/Disclaimer of Warranty: While the publisher and author(s) have used their best efforts in preparing this book, they make no representations or warranties with respect to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 409 publications
1
21
0
Order By: Relevance
“…The protein profile and overall arrangement of bands in wheat, quinoa and amaranth flours well-compared with previous studies in which the same protein profiles were observed on Protein 230 Loac or SDS gels (Hager et al, 2012;Alonso-Miravalles and O'Mahony, 2018). Wheat flour was mainly characterized by the presence of protein bands in the 43-55 kDa range which could represent gliadins and the low molecular weight glutenins (Bradová and Matějová, 2008;Juhász et al, 2015). In amaranth and quinoa flours, the presence of the typical proteins amaranthin and chenopodin, respectively, was ascertained in the A1 and A2 areas which represent the region generally modified during fermentation (Lacaze et al, 2007).…”
Section: Discussionsupporting
confidence: 61%
“…The protein profile and overall arrangement of bands in wheat, quinoa and amaranth flours well-compared with previous studies in which the same protein profiles were observed on Protein 230 Loac or SDS gels (Hager et al, 2012;Alonso-Miravalles and O'Mahony, 2018). Wheat flour was mainly characterized by the presence of protein bands in the 43-55 kDa range which could represent gliadins and the low molecular weight glutenins (Bradová and Matějová, 2008;Juhász et al, 2015). In amaranth and quinoa flours, the presence of the typical proteins amaranthin and chenopodin, respectively, was ascertained in the A1 and A2 areas which represent the region generally modified during fermentation (Lacaze et al, 2007).…”
Section: Discussionsupporting
confidence: 61%
“…Because it is known that the six Gli loci are located on 1AS, 1BS, 1DS, 6AS, 6BS and 6DS, respectively678, we selected only the microsatellite markers located on these chromosomal arms for our analysis. Specifically, the microsatellite markers selected from the six arms were 5, 4, 6, 8, 7 and 6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that, on average, in winter wheat backgrounds, inclusion of the Gpc‐B1 allele will result in higher GPC, lower milling values, and higher mixing properties. The connection between higher GPC and higher mixing properties is well documented (Juhász et al, 2015; Torbica et al, 2007; Tea et al, 2004). It is unknown why inclusion of the Gpc‐B1 allele would lead to lower milling values.…”
Section: Resultsmentioning
confidence: 93%